(untitled) - 1951-; 1936-; Kaufman, Philip; 1940-; Hurt, John; 1957-; Winstone, Ray; 1986-; LaBeouf, Shia; Allen, Karen; Blanchett, Cate; 1942-; et al. (Hollywood, Calif., 2008)
Indy tries to outrace a brilliant and beautiful agent for the mystical, all-powerful Crystal Skull of Akator. Teaming up with a rebellious young biker and his spirited love Marion, Indy takes you on a breathtaking, action- packed adventure.
Keywords: Jones, Indiana (Fictitious character); Drama; Adventure and adventurers; Drama; Crystals; Drama; Action and adventure films; Feature films; Video recordings for the hearing impaired